Modeling self-sovereign identity governance framework - Sroor, Maha (2022)
Digital identity has become a topic that attracts the attention of researchers due to the enormous number of digital services that have been provided online recently. Researchers face many obstacles regarding the security, privacy, and utility of digital identity. Self-Sovereign Identity (SSI) ecosystems provide a solution for digital identity and provide a decentralized human-centric paradigm that enables users to own and control their identity. The governance framework (GF) is a crucial challenge in building SSI ecosystems for two reasons. Firstly, the governance framework needs to address various aspects such as user needs, standards, laws, and business requirements in the ecosystem. Secondly, the ecosystem consists of a diverse, dynamic, and distributed group of stakeholders. This work adopts a new methodology for developing a governance framework by providing a visual view of the SSI ecosystem. In addition, it seeks to highlight the importance of domain-specific modeling in developing governance frameworks. It also addresses empirical observations from a real case study and the modeling journey that supported the creation of the governance framework. The advantages, challenges of modeling, and the modeling tool used are discussed based on the evaluation from the case feedback and conclude with fu ture work.